Dexter Library Reference Room, circa 1950 (1950)
Caption reads: 'Reference reading room of the library, capable of seating approximately 250 at one time. Not shown is a recreational browsing room with fireplace, leather upholstered furniture, tables, etc., at the south end of this wing.'